2014
DOI: 10.1038/ncomms4211
|View full text |Cite
|
Sign up to set email alerts
|

Long livestock farming history and human landscape shaping revealed by lake sediment DNA

Abstract: The reconstruction of human-driven, Earth-shaping dynamics is important for understanding past human/environment interactions and for helping human societies that currently face global changes. However, it is often challenging to distinguish the effects of the climate from human activities on environmental changes. Here we evaluate an approach based on DNA metabarcoding used on lake sediments to provide the first high-resolution reconstruction of plant cover and livestock farming history since the Neolithic Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
334
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(339 citation statements)
references
References 47 publications
3
334
0
2
Order By: Relevance
“…However, while detecting human impacts at local scales can be challenging for the stated reasons, recent techniques are promising, including specific biomolecular markers (see Dubois and Jacob, 2016, for a review), ancient DNA (e.g. Anderson-Carpenter et al, 2011;Domaizon et al, 2017;Giguet-Covex et al, 2014), high-resolution stratigraphy and sediment scanning techniques (e.g. Arnaud et al, 2012;Flower et al, 2012;Marquer et al, 2008) as well as wider use of macrofossils combined with stable isotope studies (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, while detecting human impacts at local scales can be challenging for the stated reasons, recent techniques are promising, including specific biomolecular markers (see Dubois and Jacob, 2016, for a review), ancient DNA (e.g. Anderson-Carpenter et al, 2011;Domaizon et al, 2017;Giguet-Covex et al, 2014), high-resolution stratigraphy and sediment scanning techniques (e.g. Arnaud et al, 2012;Flower et al, 2012;Marquer et al, 2008) as well as wider use of macrofossils combined with stable isotope studies (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…At a higher elevation site (Lake Anterne, located at 2063 m a.s.l. ), fluctuations in sedimentation are dominated by the terrigenous fraction, and follow roughly regional climate signals since at least 4000 b2k, but sedimentary ancient DNA (aDNA) demonstrated that the most intense erosion period was caused by deforestation and overgrazing by sheep and cattle during the Late Iron Age and Roman Period (400 bce-200 ce; Giguet-Covex et al, 2014). In a high alpine Lake in Switzerland (Sägistalersee, located at 1935 m a.s.l.…”
Section: Europementioning
confidence: 99%
See 1 more Smart Citation
“…DNA from both plants and plankton has been found in sediment cores spanning centennial to millennial time scales at lower latitudes (e.g. Epp et al, 2010;Stoof-Leichsenring et al, 2012;Boessenkool et al, 2014;Giguet-Covex et al, 2014), but highlatitude lakes, such as in the Arctic, can supposedly yield results going back further in time, because conditions for DNA preservation are optimal under cold conditions (Lindahl, 1993;P€ a€ abo et al, 2004;Willerslev et al, 2004;Hofreiter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Potential contamination and false detection biases were controlled for by following the recommendations of Giguet-Covex et al, 2014;Pansu et al, 2015) were run with GNU "parallel" when possible (Tange, 2011 (Hill, 1973) to estimate the effects of potential laboratory biases and biological factors of interests. The first three Hill numbers correspond to species richness (H1), the exponent of Shannon diversity (H2), and the inverse of the Simpson diversity (H3).…”
Section: Sequence Processing and Data Analysismentioning
confidence: 99%